Advanced and Effective Learning in Context Aware and Adaptive Mobile Learning Scenarios - Bhaskar, Nagella Uday; Govindarajulu, Paladugu (International Journal of Interactive Mobile Technologies (iJIM), 2009)
The ability to support students/learners to learn on the move at any place and at any time is new task to be addressed by using the mobile devices of the learners. Mobile technology support has given birth to the concept of mobile learning possessing a wide spectrum of applications and new teaching and learning techniques. This paper discusses a study conducted for undergraduate students on the effect of mobile technology usage in a learning process. The results showcased here indicate acceptance of the mobile devices into the learning process with a well appreciated enthusiasm from the learners.